Another upper bound for the domination number of a graph (1986)
If δ and  ∆ are the minimum and máximum degrees of a simple graph G of size n, then, for its domination number B(G), we show that B(G) ≤ [(n-∆-1) (n- δ-2)/(n-1)]+2.